The water-land-food nexus reveals growing resource export pressure in middle-income economies - Liu, Yuexin; Gao, Yang; Gai, Jianxun; Liu, Haowei; Zhang, Zhonghao; Diogo, Vasco; Hersperger, Anna (Resources, conservation and recycling, 2025)
Water, land, and food constitute essential components of agricultural supply chains, yet their interconnections remain unclear. Here we used the multi-regional input-output, in conjunction with the nexus index, to analyze the impact of agricultural trade on water and land efficiency. An average of 38.07 % of land use and 28.27 % of water consumption embedded in agricultural commodities was used for interregional trade from 1995 to 2015. Overall, the trading flows transferring from resource-rich and underdeveloped economies to resource-poor and developed economies enhanced the resource efficiency on a global scale, with average land and water efficiency rising by 68.23 % and 56.11 %, respectively. But the growth intensity of commodities’ exports has limited the improvement of resource efficiency in exporting countries, particularly in net middle-income exporters such as Brazil, India, and Indonesia. The pressure of land and water transfers varies across commodities. Crop-based products account for 72.39 % of water resource flow, while meat-based products account for 67.61 % of land resource flow. Among these, vegetable, fruit, and nut, which have the highest water-land-food nexus, is playing an increasingly significant role in the global pattern of resource transfer. The study proposed targeted measures for sustainable agricultural management through efficiency calculation in Water-Land-Food nexus.
Online verfügbar: 09. November 2024
Gesehen am 21.05.2025